Sex Ratio, Length-Weight Relationship and Geographic-Bathymetric Distribution of Squalus Cubensis (SQUALIFORMES: SQUALIDAE) in the Caribbean Coast of Central America - Benavides-Morera, Rosario; Brenes-Rodríguez, Carlos Luis; Márquez-Artavia, Amaru (Uniciencia, 2017)
This article describes the geographic and bathymetric distribution of Squalus cubensis; some specimens were captured during a prospecting survey campaign that was held from January 3 to February 3, 2011, aboard the R/V Miguel Oliver on the Caribbean coast of Central America. 140 individuals were captured in 96 sets (65 males and 75 females) from 24 to 100 cm in total length, and between 70 and 3,040 grs of total weight. A marked difference in the sizes was found, indicating a sexual dimorphism. The length-weight relationship between sexes showed no significant differences in the slopes of the respective regressions. The spatial distribution of catches showed that more individuals were obtained primarily in Panama at depths ranging from 250 to 950 m, followed by Honduras. Over 75% of the catch occurred in a layer of the water column with temperatures between 12°C and 17°C. This study provides important preliminary information about sex ratio and length-weight relationship in S. cubensis captured in this area.